2008
DOI: 10.2214/ajr.07.3396
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Costal Cartilage Injuries

Abstract: MRI can be a useful technique in the diagnosis of costal cartilage injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…However, FDG PET/CT is not cost-effective in the diagnosis of costal and costal cartilage fractures [10]. Moreover, the costal injury is more apparent on fat-suppressed T2-weighted coronal magnetic resonance imaging with a high signal at the injury site [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, FDG PET/CT is not cost-effective in the diagnosis of costal and costal cartilage fractures [10]. Moreover, the costal injury is more apparent on fat-suppressed T2-weighted coronal magnetic resonance imaging with a high signal at the injury site [9].…”
Section: Discussionmentioning
confidence: 99%
“…Because costal cartilage injuries are often located in the junctional regions; chondrosternal and chondrocostal, the overlapping osseous structures in these areas limit the usefulness of radiographs. A Canadian study from Subhas et al showed that cross-sectional techniques such as CT, US and MRI are more sensitive to detect these injuries ( Figure 5) (20). On CT, cartilage density is relatively uniform (70-120 HU), in which this value is higher than fat and muscle but lower than calcium ( Figure 6).…”
Section: Injuries Of the Costal Cartilagementioning
confidence: 99%
“…Also, oedema-like signal T2 could be seen in the surrounding soft tissue in recent or subacute injuries (<3 months). A fracture line, which is not always present, appears as a localized linear oedema-like decreased T1 and increased T2 signal, and it is best to be visualized on the fluid-sensitive sequences (fat-saturated fast spin-echo T2-weighted or STIR-weighted sequences) and in the coronal plane (20).…”
Section: Injuries Of the Costal Cartilagementioning
confidence: 99%
See 1 more Smart Citation
“…MRI also provides a larger field of view and depicts the complete chest including abnormalities of the surrounding mediastinum and inflammatory processes (1). Therefore, MRI has been used to assess chest wall, mediastinum, and diaphragm diseases (10,11), as well as the neonatal heart (12)(13)(14). In addition, other experimental studies on animal models have demonstrated the utility of MRI for evaluation of thoracic structures (15,16).…”
Section: Introductionmentioning
confidence: 99%